To breed or not to breed: drivers of intermittent breeding in a seabird under increasing predation risk and male bias - Markus Öst; Andreas Lindén; Patrik Karell; Satu Ramula; Mikael Kilpi (Springer, 2022)
Intermittent breeding may be adaptive for long-lived species subjected to large accessory reproductive costs, but it may also reflect reduced adaptation to the environment, reducing population growth. Nevertheless,environmental influences on breeding propensity, particularly that of predation risk, remain poorly understood and difficult to study, becausenon-breeders are typically not identified. Female eiders Somateria mollissimafrom the Baltic Sea provide an excellent testbed, because nesting females have been exposed to intensifying predation and growing male bias that may increase female harassment. We based our study on long-term data (14 years) on females captured and marked at the nest, and females individually identified at sea irrespective of capture status. We hypothesized that breeding propensity decreases with increasing predation risk and male bias, and increases with breeder age.Consistent with our hypotheses, females nesting on islands with higher nest predation risk were more likely to skip breeding, and breeding probability increased with age. In contrast, the steep temporal decline in breeding propensity could not be reliably attributed to annual adult sex ratio or to the abundance of white-tailed sea eagles (Haliaeetus albicilla),the main predator on females, at the nearby Hanko Bird Observatory. Breeding probability showed significant consistent individual variation.Our results demonstrate that spatiotemporal variation in predation riskaffects the decision to breed and high incidence of non-breeding was associated with low fledging success. The increased frequency of intermittent breeding in this declining population should be explicitly considered in demographic models, and emphasis placed on understanding the preconditions for successful reproduction.